2004
DOI: 10.1038/sj.ejhg.5201211
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization characterization of apparently balanced translocation reveals cryptic complex chromosomal rearrangements with unexpected level of complexity

Abstract: The great majority of apparently balanced translocations are associated with multiple miscarriages and normal phenotype. Several mechanisms have been proposed to explain how a small percentage of apparently balanced translocations are associated with abnormal phenotypes. One of the proposed mechanisms that have not been well investigated is that apparently balanced translocations may host 'cryptic' complex chromosomal rearrangements (CCRs). To test this hypothesis, this study investigated 20 non-preselected ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 17 publications
(16 reference statements)
2
45
0
8
Order By: Relevance
“…Looking at apparently balanced translocations, Gribble et al (2005) found in three out of ten cases additional breakpoint complexity at or near the translocation breakpoints. Similar results were obtained by Patsalis et al (2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Looking at apparently balanced translocations, Gribble et al (2005) found in three out of ten cases additional breakpoint complexity at or near the translocation breakpoints. Similar results were obtained by Patsalis et al (2004).…”
Section: Discussionsupporting
confidence: 90%
“…Since array CGH can only detect imbalanced chromosomal aberrations, other tech-niques are needed to detect balanced chromosomal rearrangements. Whole chromosome painting, M banding FISH (as illustrated for example in this study) and mFISH (Patsalis et al, 2004;Gribble et al, 2005) therefore complement high resolution array CGH and are required for the accurate delineation of the breakpoints involved and the full cytogenetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…At least 100 interphase nuclei were analyzed in each sample. The high SD-cell frequency indicated an asynchronous mode of replication, and the low frequency indicated a synchronous mode (Patsalis et al, 2004).…”
Section: Cytogenetic Evaluationmentioning
confidence: 99%
“…1A, Table 1). The Cypriot NMDB includes information for the mutation frequencies of α-thalassemia (Baysal et al, 1995, Kyriakou et al, 2000, ÎČ-thalassemia (Baysal et al, 1992), ÎŽ-thalassemia (Triffilis et al, 1993), G6PD deficiency (Drousiotou et al, 2004), cystic fibrosis (Deltas, 1998), familial hypercholesterolemia (Xenophontos et al, 2000;Baysal E, personal communication), familial Meditteranean fever (Deltas et al, 2002), GM-1 gangliosidosis type I (Georgiou et al, 2005), Sandhoff disease (Drousiotou et al, 2000), Huntington disease (Christodoulou K., unpublished), Y-linked spermatogenic failure (Ioulianos et al, 2002, achondroplasia (Patsalis PC., personal communication), Fragile X syndrome (Patsalis et al, 1999a(Patsalis et al, , 1999b, Prader-Willi, Angelman, Williams-Beuren and 22q11.2 micro-deletion syndromes (Patsalis PC, personal communication), X-linked ichthyosis, retinoblastoma (Patsalis PC, personal communication) and various rearrangements in chromosomal subtelomeric regions (Sismani et al, 2001, Patsalis et al, 2004, leading to Miller-Dieker lissencephaly (17p), Cri du Chat (5p), Wolf-Hirschhorn syndromes (4p), α-thalassemia, tuberous sclerosis and the adult form of polycystic kidney disease (16p). It should be stated that all the Turkish Cypriot mutation data pertain to the indigenous Turkish Cypriots, based on well-preserved medical records, and none of the data were derived from the settlers from Turkey who immigrated to Cyprus only after Turkey's invasion to Cyprus in 1974.…”
Section: Data Sources and Database Contentmentioning
confidence: 99%